2015
DOI: 10.5214/ans.0972.7531.220107
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and striatal histomorphology following chronic nicotine administration in female and male rats

Abstract: BackgroundNicotine is a subject of continuous research because of its likely ameliorative effects on neurologic and neurodegenerative disorders.PurposeThis study examined the effects of its chronic subcutaneous administration on hippocampal and striatal microstructure in both female and male rats.MethodsForty adult female and male Wistar rats were divided into 4 groups. Three experimental groups were administered nicotine via subcutaneous injections at doses of 0.25, 2 and 4 mg/kg body weight for 28 days. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…The pyramidal and granular layers of animals administered nicotine for 21 days, showed a transient elevation in cell count which was very apparent down the group. This hypothesis further buttresses the fact that acute administration of nicotine, lead to moderate hyperplasia and hypertrophy as previously documented and is in accordance with a work by Adeniyi and Musa in 2011 who concluded that nicotine administration caused hyperplasia in the hippocampus and that of Ijomone et al (2015), who reported hippocampal hypoplasia. [50,53] The reason for this is likely the time of administration of nicotine.…”
Section: Quantitative Analysis Of the Effect Of Nicotine Insupporting
confidence: 91%
See 4 more Smart Citations
“…The pyramidal and granular layers of animals administered nicotine for 21 days, showed a transient elevation in cell count which was very apparent down the group. This hypothesis further buttresses the fact that acute administration of nicotine, lead to moderate hyperplasia and hypertrophy as previously documented and is in accordance with a work by Adeniyi and Musa in 2011 who concluded that nicotine administration caused hyperplasia in the hippocampus and that of Ijomone et al (2015), who reported hippocampal hypoplasia. [50,53] The reason for this is likely the time of administration of nicotine.…”
Section: Quantitative Analysis Of the Effect Of Nicotine Insupporting
confidence: 91%
“…[54] The current study displayed a dose and time dependant progressive increase in neuronal population which suggests severe hyperplasia. However, this study also demonstrated that chronic administration of nicotine led to increase cell proliferation rather than neurodegeneration as noted by Adeniyi and Musa (2011), Ijomone et al (2015). [50,53] Possible reasons for the dissimilarity could be attributed to difference in mode of nicotine administration.…”
Section: Histological Changes In Hippocampussupporting
confidence: 71%
See 3 more Smart Citations